Endpoints for clinical trials of sarcoidosis - Baughman, R.P.; Drent, M.; Culver, et al., D.A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Over the past few years an increasing number of prospective controlled sarcoidosis treatment trials have been completed. Unfortunately, these studies utilize different endpoints making comparisons between studies difficult. At the recent World Association of Sarcoidosis and other Granulomatous disease (WASOG) meeting, a session was dedicated to the evaluation of clinical endpoints for various disease manifestations. These included pulmonary, pulmonary hypertension, fatigue, cutaneous, and a classification of clinical disease phenotypes. Based on the available literature and our current understanding of the disease, recommendations for clinical evaluation were proposed for each disease category. For example, it was recommended that pulmonary studies should include changes in the forced vital capacity. Additionally, it was recommended that all trials should incorporate measurement of quality of life.